2015
DOI: 10.1038/srep15269
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of dynamic cerebral autoregulation in cerebral small vessel disease: Diffuse and sustained

Abstract: Cerebral small vessel disease is a major cause of stroke and vascular dementia; however, the pathogenesis is largely unclear. In this study, we investigated the characteristics of the impairment of dynamic cerebral autoregulation (dCA) in lacunar infarction patients. Seventy-one lacunar infarction patients were enrolled in the study, including 46 unilateral middle cerebral artery (MCA) territory stroke patients and 25 unilateral posterior cerebral artery (PCA) territory stroke patients. Each group of patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(65 citation statements)
references
References 25 publications
(38 reference statements)
4
59
1
1
Order By: Relevance
“…The stability of gain and coherence in TFA has not been tested in large scale or discussed, and it seems that in a 10-minute time scale, gain and coherence may not be stable according to Deegan's and our findings. In previous studies of dCA in stroke, gain has not been reported to differ between patients and controls [ 12 , 14 , 21 , 28 ]. If gain is an unstable dCA index, it would be difficult to correlate gain with other physiologic or clinical variables.…”
Section: Discussionmentioning
confidence: 97%
“…The stability of gain and coherence in TFA has not been tested in large scale or discussed, and it seems that in a 10-minute time scale, gain and coherence may not be stable according to Deegan's and our findings. In previous studies of dCA in stroke, gain has not been reported to differ between patients and controls [ 12 , 14 , 21 , 28 ]. If gain is an unstable dCA index, it would be difficult to correlate gain with other physiologic or clinical variables.…”
Section: Discussionmentioning
confidence: 97%
“…33 studies were included comprising 18 on AIS (large artery stroke, one study that also included transient ischemic attack (TIA)), 12, 13, 26-41 six on ICH, [42][43][44][45][46][47] three on small artery stroke, including lacunar infarction, [48][49][50] and six on AIS both large and small artery stroke 2, 23-25, 51, 52 .…”
Section: Summary Of Included Studiesmentioning
confidence: 99%
“…13, 24, 27, 29, 32, 35-38, 43, 46 Moreover, the majority of participants were recruited within 6 to 72 hours from stroke onset, 2, 12, 13, 24-27, 29, 34-40, 42, 43, 45-47, 49, 51 including within 48 hours (n = 8), 2, 25, 34-36, 39, 47, 49 five studies assessed dCA at 72 hours, 24,29,40,45,51 twenty-four hours were studied in four studies, 37,42,43,46 three studies examined dCA between 30 to 37 hours, 12,13,38 dCA was assessed at 6 hours (n = 2), 26,27 one study assessed between onset to 16 days, 52 other three studies recruited participants after first week of stroke onset 32,33,48 and one study examined recovery at 6 months. 49 The location of the lesion was identified in the MCA (n = 13), 23, 26-28, 33-37, 40, 41, 49, 51 posterior cerebral artery (n = 3), 31,32,49 and anterior cerebral artery territories (n = 3), 2, 25, 52 though eight studies did not specify the precise localization of the lesion. 12,13,24,29,38,39,48,50 Five studies of ICH recruited participants for dCA testing within 48 hours of onset, 42,43,[45][46][47] with the exception of one study which assessed at 4-6 days after onset.…”
Section: Participant Characteristicsmentioning
confidence: 99%
“…Loss of blood flow regulation occurs in a variety of cerebrovascular conditions, both in acute stroke(25-27), and in chronic cerebrovascular conditions such as small vessel disease(28, 29), metabolic syndrome(30, 31), and high grade carotid artery stenosis(32-34). Poor blood flow is an important predictor of stroke risk.…”
Section: Discussionmentioning
confidence: 99%